ANALISIS KINERJA KEUANGAN PERBANKAN DI INDONESIA DAN MALAYSIA - Fitria Marisya (Program Magister Manajemen Indo Global Mandiri University, 2021)
This research focuses on the analysis of Bank Financial Performance in Indonesia and Malaysia in 2010 - 2014. The study tries to discover the influence of NPL (non performing loans), Good Corporate Governance (GCG), Operational Expenses Compared to Operational Revenue (BOPO) and Capital Adequacy Ratio (CAR) toward profitability (ROA) of banking Indonesia and Malaysia. Using the purposive sampling technique, 54 banks, 27 in Indonesia and 27 in Malaysia, were used as sample. The data were analyzed using multiple regression analysis. The result show that (1) NPL partially gives negative siqnificant contribution toward ROA of banks in Indonesia and Malaysia, while GCG, BOPO, and CAR partially give positive siqnificant contribution toward it; (2) NPL, GCG, BOPO and CAR simultaneously give positive significant contribution toward ROA of banks in Indonesia and Malaysia. The result of this study might be a metter of consideration for investor in taking decision in investment particularly in banking sector both in Indonesia and Malaysia.